STUDI EKSPERIMENTAL PEREMAJAAN ASPAL TUA PG 76 DENGAN REJUVENATOR MINYAK GORENG BEKAS (MGB) - Adi Pratama, Tegar; Wahab, Wahyuni (Ensiklopedia of Journal, 2025)
Pavement is one of the most important things to support smooth transportation to create a sense of comfort and safety for road users. Seeing the very high increase in population mobility, it is necessary to improve the quality of road transportation infrastructure development that is environmentally friendly, cheap and durable. For this reason, it is necessary to innovate pavement methods that are able to produce quality that meets the standards, but by using the minimum material possible. One of the environmentally friendly pavements is using the recycling method. recycling method is a method used to repair damaged pavement. This recycling method has several advantages, including restoring the strength of damaged pavement and overcoming dependence on new materials. in this research, PG 76 asphalt type material was used with used cooking oil as a rejuvenator and the percentage used in this study was 1%; 1.5%; 2%; 2.5%; and 3% of the weight of old asphalt.